Comparison of Task-Oriented and Bobath-Based Trunk Training on Balance, Functional abilities and Walking in Ischemic Stroke Patients - Fatima Younas, Hira Shafiq, Sara Khan, Saweera Saleem, Azhar Mehmood, Adnan Ikram (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the outcome of task oriented and bobath based trunk training on balance in ischemic stroke patients Study design: Randomized controlled trial Place and duration: Physical Therapy department, Younas health care Hospital Shahdara Methodology: Sixty-six patients rewarding the inclusion and exclusion criteria were assigned in two groups, Group 1 and Group 2. Group 1 was given conventional treatment + Task oriented trunk and Group 2 was given receive Convention treatment + Bobath based trunk training. Participants in both groups were joined in a 12-week physiotherapy session that seen three days a weekly for one sixty minute respectively day. They stayed examined at starting point and after the 12-week mark. Berg Balance Scale and Trunk impairment scale were used as outcome measures. Results: The adjustment score of BBS was 8.93 (6.32-11.54) that helps in investigational set (P<0.001). Furthermore, variation score of the Trunk Impairment Scale between the groups was 3.34 (1.48-4.91). It also helps the Task-oriented group with (P<0.001). However, task-oriented approach is more effective. Conclusion: Exercises performed with task-oriented approach are more effective to improve balance and functions of the patients with ischemic stroke as associated to patients who were treated with Bobath approach. Besides, better improvement has been found on purposeful balance suggesting the surplus effects with task-oriented exercise. Keywords: Stroke, Bobath, Task-oriented, Balance